Compulsory medical measures in criminal law of neighbouring countries - Markava, Nastassia M. (Journal of the Belarusian State University. Law, 2019)
This article analyzes the rules on coercive measures of a medical nature in the legislation of neighboring countries and the application of such measures to the persons suffering from mental illness or drug addiction and committed socially dangerous acts. For the correct understanding of the provisions of the coercive measures of a medical nature and prospects of further development of this institution it is important to study foreign legislator positions for fixing of compulsory medical measures in the criminal law. Analyzed legislation states former members of the USSR, investigated the main issues of regulation and the application of these measures. Considered provisions relating to the grounds and purpose of the application of compulsory medical measures, their types, categories of persons to whom these measures apply, and the application of those measures. On the basis of the study are summarized and presented the findings of the legislative consolidation of compulsory medical measures in the foreign criminal law.
Keywords: compulsory medical measures; security measures; regulation; criminal law; foreign states; neighboring countries